Onion Yield, Resource Used and Farm Income as Affected by National Fadama Development Project (NFDP) in Kebbi State, Nigeria - Aliyu Danmaigoro; Ibrahim R (International Journal of Integrative Research, 2023)
The impact of National Fadama Development Project (NFDP) on onion yield, resource used and farm income in some selected Kebbi State local government areas was examined. Purposive selection was used to select five local government areas for the study. Random sampling technique to select respondents and structured questionnaire and interview schedules were administered to collect data. The data obtained were analyzed using descriptive statistics, t-test, x2 test, farm budgeting and production function analysis. The results show that, majority of the respondents acquired their fadama land through inheritance, members obtained high yields than non-members, variable costs dominated product costs, members earned more profit than non-members. All the estimated co-efficients were positive. There was over utilization of all inputs except fixed capital, it is profitable to produce in the study area, major constraints include inadequate inputs, credit and storage facilities. Agricultural production and farmer’s income can be increase if the existing challenges are addressed.